clinical prognostic factors after the first attack of early onset multiple sclerosis in iraq - Al hamadani, Hasan A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Paediatric-onset multiple sclerosis (MS) has been a focus of great interest in recent years. The prognostic factors in early onset of MS have been evaluated in few studies with various methodologic approaches, and the discussion about the existence of clinical courses different from that of adult-onset MS is still open.